Bitcoin, economic policy uncertainty and geopolitical risk: a systematic review - Thong, Li Yi; Chia, Ricky Chee Jiun; Mohd Fahmi Ghazali (Human Resource Management Academic Research Society, 2024)
Among all the cryptocurrencies in the market, Bitcoin is the most widely discussed and most popular cryptocurrency in the cryptocurrency market. This study aims to review and summarize the existing literature findings pertaining to the impact of geopolitical risk and economic policy uncertainty on Bitcoin. The results shown geopolitical risk and economic policy uncertainty have predictive power on Bitcoin prices. Both economic policy uncertainty and geopolitical risk have positive and negative effects on Bitcoin. The geopolitical risk and economic policy uncertainty able serve as a hedging instrument against Bitcoin. Bitcoin also can act as a safe haven against geopolitical risk and economic policy uncertainty. A summary of further implication from previous study suggested utilizing other uncertainty measures, applying other cryptocurrency, exploring Bitcoin’s relationship with other financial assets, and employing alternative methodologies.